Considerations for Youth Sports (Centres for Disease Control and Prevention, 2020)
As some communities in the United States begin to start youth sports activities again, the Centers for Disease Control and Prevention (CDC) offers the following considerations for ways in which youth sports organizations can protect players, families, and communities and slow the spread of the Coronavirus Disease 2019 (COVID-19). Administrators of youth sports organizations can consult with state and local health officials to determine if and how to put into place these considerations. Each community may need to make adjustments to meet its unique needs and circumstances. Implementation should be guided by what is practical, acceptable, and tailored to the needs of each community. These considerations are meant to supplement - not replace - any state, local, territorial, or tribal health and safety laws, rules, and regulations with which youth sports organizations must comply.